EFFECT OF LACTATION STAGES ON SOME SERUM LIPID PARAMETERS IN UPGRADED MURRAH BUFFALOES - Rajoriya, Shweta; Tiwari, Sheela; Gupta, RS; Rajoriya, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was carried out to investigate the changes in serum lipid profile in different lactation stages in upgraded Murrah buffaloes (n=6). The entire lactation period was divided in three successive stages – early (0-13 weeks), mid (14-26 weeks) and late lactation stage (27-40 weeks). Blood samples were collected from each lactation stage and analyzed for total serum cholesterol, HDL cholesterol, LDL cholesterol and triglycerides. The results revealed that all the parameters differed significantly amongst the three lactation stages, except LDL cholesterol. The serum total cholesterol, HDL cholesterol and triglycerides increased from early to mid lactation and then declined significantly.
Keywords: lipid profile; buffalo; lactation; Cholesterol